2015
DOI: 10.1111/tpj.12787
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of acyl‐lipids in Chlamydomonas reinhardtii

Abstract: SUMMARYMicroalgae are emerging platforms for production of a suite of compounds targeting several markets, including food, nutraceuticals, green chemicals, and biofuels. Many of these products, such as biodiesel or polyunsaturated fatty acids (PUFAs), derive from lipid metabolism. A general picture of lipid metabolism in microalgae has been deduced from well characterized pathways of fungi and land plants, but recent advances in molecular and genetic analyses of microalgae have uncovered unique features, point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
273
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(278 citation statements)
references
References 145 publications
(247 reference statements)
4
273
0
1
Order By: Relevance
“…PG is a major lipid of chloroplast membranes, alongside the nonphosphorous glycoglycerolipids monogalactosyldiacylglycerol, diagalactosyldiacylglycerol, and sulfoquinovosyldiacylglycerol. PG is thought to be mostly synthesized in the chloroplast from prokaryotic pathway PA, although additional synthesis in the ER cannot be discounted (Boudière et al, 2014;Li-Beisson et al, 2015). Indeed the localization of either PGPS isoform is unknown, with one predicted to be chloroplastic and the other nonchloroplastic (Hung et al, 2015;Li-Beisson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PG is a major lipid of chloroplast membranes, alongside the nonphosphorous glycoglycerolipids monogalactosyldiacylglycerol, diagalactosyldiacylglycerol, and sulfoquinovosyldiacylglycerol. PG is thought to be mostly synthesized in the chloroplast from prokaryotic pathway PA, although additional synthesis in the ER cannot be discounted (Boudière et al, 2014;Li-Beisson et al, 2015). Indeed the localization of either PGPS isoform is unknown, with one predicted to be chloroplastic and the other nonchloroplastic (Hung et al, 2015;Li-Beisson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PG is thought to be mostly synthesized in the chloroplast from prokaryotic pathway PA, although additional synthesis in the ER cannot be discounted (Boudière et al, 2014;Li-Beisson et al, 2015). Indeed the localization of either PGPS isoform is unknown, with one predicted to be chloroplastic and the other nonchloroplastic (Hung et al, 2015;Li-Beisson et al, 2015). It is unclear whether the PG inhibition within the GPD3-OE lines is due to reduced chloroplastderived PG, perhaps due to up-regulated and overcompensated eukaryotic pathway activity or reduced ER-derived PG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for algal physiology, including lipid metabolism (Merchant et al, 2012;Li-Beisson et al, 2015). Initial experiments showed no significant differences in heptadecene content between the vegetative cells of the strains CC124 (mating type: minus) and CC125 (mating type: plus) (Supplemental Fig.…”
Section: Heptadecene Content Varies With Growth Stage and Culture Conmentioning
confidence: 99%
“…Three studies on the presence of lipid droplets in the chloroplast have reported two lines of evidence: one based on starchless mutants under nitrogen-deficient conditions (Fan et al, 2011;Goodson et al, 2011) and the other based on wildtype cells under high-light stress (Goold et al, 2016). Localization of the lipid droplets is crucial to engineering microalgae for biofuel production, which relies on the biochemical and cytological understanding of TAG synthesis and accumulation (Merchant et al, 2012;Johnson and Alric, 2013;Li-Beisson et al, 2015). Thus, we sought to resolve the controversy by carefully repeating the previous electron microscopy experiments and using confocal 3D image reconstruction.…”
mentioning
confidence: 99%